Integration-Interconnection with a Scientific Approach on the Rational and Irrational Inequality of One Variable Module - Ulwiyah, Sa'adatul; Permatasari, Dian; Laksmiwati, Pasttita Ayu (Universitas Negeri Malang, 2022)
Learning in madrasah tends to teach concepts and materials related to that science alone, without paying attention to other sciences. Thus, there is a need for innovation in learning that can link various fields of science, one of which is by applying integration-interconnection-oriented learning. The research aims to develop insights into integrated-interconnected mathematical learning modules with a scientific approach to rational and irrational materials of one variable is valid. The type of research used is research and development (R&D). This research was designed by following the steps of Richey and Klein's development, namely the PPE development model (Planning, Production, and Evaluation). The instrument used is a product validation assessment sheet given to two expert validators. The results showed that the integrated-interconnection-oriented mathematics learning module with a scientific approach that had been developed got an average product validity score of 0.82 with a high category. Thus, it can be concluded that this learning module has met the valid criteria.